Liquid-liquid separation in gut immunity - Wang, Zhaoyang; Zhou, Lili; Zhong, Xiaolan; Jiang, Yiguo; Zhang, Zhentao; Li, Wanglin (Frontiers in Immunology, 2024)
Gut immunity is essential for maintaining intestinal health. Recent studies have identified that intracellular liquid-liquid phase separation (LLPS) may play a significant role in regulating gut immunity, however, the underlying mechanisms remain unclear. LLPS refers to droplet condensates formed through intracellular molecular interactions, which are crucial for the formation of membraneless organelles and biomolecules. LLPS can contribute to the formation of tight junctions between intestinal epithelial cells and influence the colonization of probiotics in the intestine, thereby protecting the intestinal immune system by maintaining the integrity of the intestinal barrier and the stability of the microbiota. Additionally, LLPS can affect the microclusters on the plasma membrane of T cells, resulting in increased density and reduced mobility, which in turn influences T cell functionality. The occurrence of intracellular LLPS is intricately associated with the initiation and progression of gut immunity. This review introduces the mechanism of LLPS in gut immunity and analyzes future research directions and potential applications of this phenomenon.